Quantum Storage of Three-Dimensional Orbital-Angular-Momentum Entanglement in a Crystal - Zhou, Zong-Quan; Hua, Yi-Lin; Liu, Xiao; Chen, Geng; Xu, Jin-Shi; Han, Yong-Jian; Li, Chuan-Feng; Guo, Guang-Can (Physical review letters, 2015)
Here we present the quantum storage of three-dimensional orbital-angular-momentum photonic entanglement in a rare-earth-ion-doped crystal. The properties of the entanglement and the storage process are confirmed by the violation of the Bell-type inequality generalized to three dimensions after storage (S=2.152±0.033). The fidelity of the memory process is 0.993±0.002, as determined through complete quantum process tomography in three dimensions. An assessment of the visibility of the stored weak coherent pulses in higher-dimensional spaces demonstrates that the memory is highly reliable for 51 spatial modes. These results pave the way towards the construction of high-dimensional and multiplexed quantum repeaters based on solid-state devices. The multimode capacity of rare-earth-based optical processors goes beyond the temporal and the spectral degree of freedom, which might provide a useful tool for photonic information processing.